Error annotation and analysis of a (semi-)specialised English-French learner translation corpus - Kübler, Natalie; Mestivier, Alexandra; Pecman, Mojca (Meta, 2024)
This study aims to identify students’ main difficulties when translating (semi-)specialised texts on the basis of an error-annotated English-French learner translation corpus. Students are M1 students in a translation training programme. The corpus contains two textual genres, namely research articles and popularisation articles. We use the same translation error annotation scheme for both text types as well as a corpus-based analysis. We then aim to identify and compare the difficulties students encounter based on genres and register. The results show that the translations of popularisation texts contain more content transfer errors, which may be due to students’ tendency to take more risks when translating these, as they may feel more confident. They also show that the translations of popularisation texts contain fewer terminology errors, most probably due to lower terminological density which characterises this type of text. However, our study also shows that these differences prove to not be statistically significant, which implies that content transfer errors and terminology errors are as important in specialised as in popularisation articles translations.